(untitled) (International journal of medical sciences, 2026)
Polytrauma represents a serious medical condition characterized by multiple traumatic injuries affecting different body systems simultaneously. It remains one of the leading causes of mortality and long-term disability worldwide, particularly among young and economically active populations. The purpose of this study is to examine preventive strategies and practical measures aimed at reducing the incidence and severity of polytrauma. The research applies a qualitative analytical approach based on clinical observations, public health strategies, and trauma management principles. The findings indicate that effective prevention requires a multidisciplinary approach combining road safety policies, workplace regulations, public awareness programs, and improvements in emergency medical systems. The study concludes that systematic prevention strategies significantly decrease trauma-related morbidity and mortality while improving overall public health outcomes.